Pengaruh Pertumbuhan Ekonomi dan Kemiskinan terhadap Distribusi Pendapatan di Provinsi Jawa Tengah 2015-2022: Indonesia - Sholeh, Muh Helmi (Ekopem: Jurnal Ekonomi Pembangunan, 2024)
The research conducted by the author aims to find out how the influence of economic growth and poverty on income distribution in Central Java Province. where economic growth is based on the GRDP of Central Java Province, poverty is based on the poverty index in Central Java and income distribution is measured by the Gini Ratio of Central Java with each period is 2015-2022, this study uses secondary data, where the data is obtained from the Central Java Statistics Agency (BPS Central Java) which is accessed through the official Central Java BPS website page. In this study, the data analysis method used is multiple linear regression analysis, t test, F test and coefficient of determination. From this can be obtained the results of multiple linear regression equation Y = -121.771 + 8.052E-7 X1 - 0.002 X2. The results showed that economic growth has no effect on income distribution, while poverty has a negative effect on income distribution in Central Java Province. The coefficient of determination (R2) value is 0.392 or 39.20%, this shows that the research variables of population growth and poverty have an effect of 39.20% on income distribution, and the remaining 60.80% is influenced by other factors not examined in this study. The results of the t test show that the two independent variables (economic growth and poverty) partially have no significant effect on income distribution.